1996
DOI: 10.1017/s1357729800015071
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phenotypic relationships between performance test and reproduction traits in Large White pigs

Abstract: Genetic and phenotypic relationships between performance test and reproduction traits were estimated, after five generations of divergent selection for components of efficient lean growth, in a population of Large Wltite pigs. On ad-libitum feeding, a total of 4334 pigs were performance tested, of which 884 selected gilts had measurements of reproduction traits. On a restricted feeding regime, 1558 pigs were tested, which included 336 selected gilts with reproduction records. For pigs given food ad libitum, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
3

Year Published

1998
1998
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 14 publications
3
6
0
3
Order By: Relevance
“…Bereskin (1984), Ferguson et al (1985), Cleveland et al (1988) and Kerr and Cameron (1996) reported negative genetic correlations of fattening and slaughter traits with reproductive traits. The correlations between weight gain and number of piglets per litter on day 21 were estimated by Bereskin (1984) to be r = -0.60.…”
Section: Discussionmentioning
confidence: 95%
“…Bereskin (1984), Ferguson et al (1985), Cleveland et al (1988) and Kerr and Cameron (1996) reported negative genetic correlations of fattening and slaughter traits with reproductive traits. The correlations between weight gain and number of piglets per litter on day 21 were estimated by Bereskin (1984) to be r = -0.60.…”
Section: Discussionmentioning
confidence: 95%
“…Correlated responses in LS traits in a landrace line selected for 200 day weight, however, produced relationships that were small, and regression coefficients for reproductive traits that did not differ significantly from zero (Kuhlers & Jungst 1993). Kerr & Cameron (1996) estimated genetic and phenotypic relationships between performance test and reproduction traits, after five generations of divergent selection for daily food intake, lean food conversion and lean growth rate in 865 ad-libitum fed large white pigs. They concluded that selection directed to increase lean growth rate and/or reduce daily food intake may have a negative effect on reproductive performance, even though estimates of the genotypic and environmental correlations between traits were small.…”
Section: Relationship Between Body Weight or Size And Litter Size Or mentioning
confidence: 97%
“…Genetic correlations of piglet or litter weights at birth or weaning have been found to be consistently positive with daily gain and negative (i.e. favourable) with backfat by Tholen et al (1996), Cameron (1996a), andHermesch et al (2000). However, correlated responses in litter birth (or weaning) weights to selection for high lean growth in other studies have been either negative (DeNise et al, 1983;Fredeen and Mikami 1986) or non-significant (Cleveland et al, 1988;Chen et al, 2001;Gibson et al, 2001).…”
Section: Correlated Responsesmentioning
confidence: 99%